Stimulus-responsive shape memory materials: A review - Sun, L.; Huang, W.M.; Ding, Z.; Zhao, Y.; Wang, C.C.; Purnawali, H.; Tang, C. (Materials in engineering, 2012)
Stimulus-responsive materials are able to response to a particular stimulus, such as, heat, chemical, and light. As such, they are smarter and more intelligent than ordinary materials. While in most stimulus-responsive materials, the result is limited to a change in their certain physical/chemical properties, stimulus-responsive shape memory materials (SMMs) are able to recover their original shape, after being quasi-plastically distorted. SMMs are ideal for an integrated intelligent system, in which “The material is the machine” that can sense and then generate reactive motion as pre-programmed. This paper presents a brief review on the current progress in stimuli-responsive SMMs, from recent development in traditional shape memory alloys (SMAs) and shape memory polymers (SMPs) to newly emerged shape memory hybrids (SMHs), which open the door for ordinary people to design their own SMMs in a do-it-yourself (DIY) manner. The focus of this review is on twofold, namely phenomena, in particular those newly observed ones, and novel applications with great potential at present and in near future.